Water ecological health evaluation of urban river: a case study of Zaogang River, China - Zhang, Jiaqi; Xiang, Jiaqi; Ma, Qiwen; Li, Chunhui; Xu, Xiangen (Frontiers in Ecology and Evolution, 2024)
The ecological health of urban rivers serves as a critical indicator of the overall health of urban ecosystems. The water ecological health status of the Zaogang River in Changzhou City was evaluated; nine sections of the river and the Old Zaogang River were sampled, and an assessment system with 8 indexes for hydrologic integrity, physical structural integrity, chemical integrity, and biological integrity was set up. A comprehensive scoring system, based on index scores and their corresponding weights, was employed to evaluate the ecological health of the Zaogang River. The assessment revealed that most sections of the Zaogang River were in a healthy state, classified as second-class level. In contrast, the Old Zaogang River exhibited sub-health conditions in one section, indicating a need for comprehensive restoration measures. Water ecological health evaluation system constructed in this study is relatively complete and comprehensive, and provides a good example for the rapid evaluation of urban rivers. Additionally, the findings of the study offer guidance for managing rivers in Changzhou city.